The concept of religious security: methodological approaches of academic religious studies - Колодний, А.; Филипович, Л. (Київський національний університет імені Тараса Шевченка, 2020)
The article considers the methodological approaches used by academic religious scholars in forming the concept of religious security, in particular in Ukraine. A complete and holistic strategy or program "Religious security of Ukraine" does not yet exist, but it is being actively developed. In general, security is understood as a state in which no one and nothing threatens anyone or anything.The authors define the religious security of Ukraine as the protection of its spiritual and religious space from aggression, destruction, interference, imposition, coercion, correction, etc. by other non-Ukrainian structures, organizations, states, people who are aimed at blur and the destruction of the Ukrainian world, reducing its resistance to all other worlds.The authors analyze in detail the external and internal factors of religious security of Ukraine, which threaten its independence and autonomy, individual and collective identity.Based on this analysis, it is concluded that the Concept of national and religious security should contain provisions that ensure the free confession of faith by every citizen of Ukraine with the freedom of the religious communities functioning. The authors formulate the methodological approaches of Ukrainian academic religious studies that will allow to build this Concept. Among them: 1) worldview focus on building Ukrainian world, which is understood as a society dominated by Ukrainian values, Ukrainian visions, constructively change post-Soviet and Russian stereotypes and forms of interaction between people and social structures to specifically Ukrainian; 2) upholding the value of religious freedom and the plurality of religious life in Ukraine; 3) to affirm the openness of the religions existing in Ukraine, when one or another religious system is not closed to different tradition, but is open for communication with other institutions of both the secular and religious world; 4) to practice a new format of communication, which is possible only through and in the form of dialogue: dialogue between Church and State, Church and society, Church and Church; 5) to assist the state and its representatives in implementing the policy of equality with regard to religious organizations; 6) rely on the professionalism of experts and the responsibility of the media in objective coverage, scientific analysis and large-scale dissemination of information about the religious life of Ukraine. All this should contribute to the dominance of stability, predictability, legality, mutual understanding and cooperation of representatives of both the religious and state spheres, both secular and religious segments of Ukrainian society.

Розглянуто методологічні підходи, якими користуються академічні релігієзнавці у процесі формування концепції релігійної безпеки, зокрема України. Завершеної і цілісної стратегії або програми "Релігійна безпека України" поки що не існує, але фахівці активно ведуть її розробку. Загалом безпеку розуміють як стан, за якого ніхто і ніщо нікому і нічому не загрожує.Визначено поняття релігійної безпеки України як захищеність свого духовного і релігійного простору від агресії, руйнування, втручання, нав'язування, примушування, корегування тощо з боку інших неукраїнських структур, організацій, держав, людей, що спрямовані на розмиття та знищення українського світу, зменшення його опірності всім іншим світам.Докладно проаналізовано зовнішні і внутрішні чинники релігійної безпеки України, що загрожують її незалежності і самостійності, індивідуальній та колективній ідентичності.На основі аналізу зроблено висновок про те, що Концепція національної безпеки має містити положення, що забезпечують вільне сповідування віри кожним громадянином України за умови свободи функціонування релігійних спільнот. Сформульовано ті методологічні підходи українського академічного релігієзнавства, що дозволять вибудувати концепцію, зокрема: 1) світоглядна орієнтація на побудову свого українського світу, який слід розуміти як суспільство, де панують українські цінності, українські візії, конструктивно змінювати пострадянські і російські стереотипи та форми взаємодії між людьми і суспільними структурами на питомо українські; 2) відстоювання цінності релігійної свободи і плюральності релігійного життя в Україні; 3) утвердження відкритості існуючих в Україні релігій, коли та чи інша релігійна система не замикається на своїй традиції, а відкрита для взаємодії з іншими інституціями як секулярного, так і релігійного світу; 4) практикування нового формату спілкування, який можливий лише через й у формі діалогу: діалогу церкви і держави, церкви і суспільства, церкви і церкви; 5) сприяння державі та її представникам у впровадженні політики рівності щодо релігійних організацій; 6) покладання на професіоналізм експертів і відповідальність ЗМІ в об'єктивному висвітленні, науковому аналізі та масштабному поширенні інформації про релігійне життя України. Усе це має сприяти пануванню стабільності, прогнозованості, законності, взаєморозуміння і співпраці представників як релігійної, так і державної сфери, як світського, так і релігійного сегментів українського соціуму.
Концепція релігійної безпеки: методологічні підходи академічного релігієзнавства
Keywords: national interests; religious security; religious danger; Ukraine; religious centers; methodological approaches; національні інтереси; релігійна безпека; релігійна небезпека; Україна; релігійні центри; методологічні підходи